The association between the size of adipocyte-derived extracellular vesicles and fasting serum triglyceride-glucose index as proxy measures of adipose tissue insulin resistance in a rat model of early-stage obesity - Delgadillo-Velázquez, Jaime; Alday, Efrain; Aguirre-García, María Magdalena; Canett-Romero, Rafael; Astiazaran-Garcia, Humberto (Frontiers in Nutrition, 2024)
Obesity is a complex disease that predisposes individuals to cardiometabolic alterations. It leads to adipose tissue (AT) dysfunction, which triggers insulin resistance (IR). This suggests that people with obesity develop local IR first and systemic IR later. AT secretes extracellular vesicles, which may be physiopathologically associated with the development of IR. Our aim was to evaluate the effect of a high-fat diet on different parameters of adiposity in a rat model of early-stage obesity and to determine if these parameters are associated with markers of systemic IR. In addition, we sought to explore the relationship between fasting blood measures of IR (Triglycerides/High Density Lipoproteincholesterol [TAG/HDL-c] and Triglycerides-Glucose Index [TyG Index]) with the size of adipocytederived extracellular vesicles (adEV). We used a model of diet-induced obesity for ten weeks in Wistar rats exposed to a high-fat diet. Final weight gain was analyzed by Dual X-ray absorptiometry. Visceral obesity was measured as epididymal AT weight. IR was evaluated with fasting TyG Index & TAG/HDL-c, and adEV were isolated from mature adipocytes on ceiling culture. In the high-fat diet group, glucose and triglyceride blood concentrations were higher in comparison to the control group (Log2FC, 0.5 and 1.5 times higher, respectively). The values for TyG Index and adEV size were different between the control animals and the high-fat diet group. Multiple linear regression analyses showed that adEV size can be significantly associated with the TyG Index value, when controlling for epididymal AT weight. Our results show that lipid and glucose metabolism, as well as the size and zeta potential of adEV are already altered in early-stage obesity and that adEV size can be significantly associated with liver and systemic IR, estimated by TyG Index.